Band Pass Filter for Wideband Radar and EW Applications - Rathod, Somsing; Kumar, Atul; S Beenamole, K; P Ray, k (International Journal of Engineering and Technology, 2018)
The proposed design of wideband Band Pass Filter (BPF) utilizes composite filter design technique. This filter is used to achieve 3-dB bandwidth of 1-6GHz with more than 140% of Fractional Bandwidth (FBW). The fundamental design of composite BPF utilizes stepped impedance, Low Pass Filter (LPF) along with the quarter wavelength (Î»g/4) short circuited stubs. Î»g/4 short circuited stubs are incorporating High Pass Filter (HPF) response which transforms overall design into BPF. A modified design is developed with the help of a 3dB power divider and power coupler at input and output port respectively, to improve the roll-off at the lower cut-off frequency of the bandwidth. Both fundamental design and modified design are simulated and fabricated. Both simulated and measured results are presented, which are in agreement. This design is useful for wideband Radar and Electronic Warfare (EW) system.Â